Asegurando un equilibrio entre los intereses públicos y privados en la implementación de las medidas de cuarentena - Yaroslav Lazur; Tetyana Karabin; Oleksander Martyniuk; Oleksandr Bukhanevych; Oksana Kanienberh-Sandul (Universidad Hemisferios, 2020)
Under the influence of the spread of coronavirus infection, the world community has faced difficult challenges that provoke changes in the seemingly already stabilized legal regulation, putting at risk the settlement of human rights and the common good. The study aims to find effective mechanisms for balancing human rights and public interests in the context of their legal regulation. Specifically, this study is focused on the mechanisms of balancing private and public interests in the implementation of quarantine measures in the Covid-19 pandemic. The research methods were both general scientific and special methods, in particular: formal legal, historical and legal, analysis and synthesis. To perform the tasks of the work, the following structure was used: after some initial precisions, there are provided some considerations about the fiscal stimulus measures and about the exercise of the right of derogation; then, the study deals with the problem of lawmaking in a pandemic; and finally it is considered the threats to intellectual property in the sphere of healthcare. The results of the work show that the pandemic has seriously hit the balance between private and public interests. The public interests of the government and society have become a priority, but in many cases, the measures that infringe private interests are disproportionate, untimely and inefficient.